2014
DOI: 10.1177/0020852313509553
|View full text |Cite
|
Sign up to set email alerts
|

All motivated by public service? The links between hierarchical position and public service motivation

Abstract: International audienceResearch into public service motivation is currently witnessing exponential growth. However, the universal application of the concept to all categories of public employees raises questions. Indeed, the origins of the concept, which can be traced back to political science studies in the United States, may suggest that the concept applies mainly to senior management but much less to operatives of various types, whose motivations seem more instrumental . Research into the antecedents of PSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 28 publications
1
12
0
1
Order By: Relevance
“…Table A2 categorizes the same articles based on the measure of PSM used in each study. The columns are as follows: Alonso and Lewis (2001) x Andersen (2009) x Andersen and Pedersen (2012) x Andersen and Serritzlew (2012) x Bellé (2013) x x x x Brewer and Selden (1998) x Brewer, Selden, and Facer (2000) x Bright (2005) x Bright (2007) x Caillier (2013) x Caillier (2014) x Christensen and Wright (2011) x x x Coursey, Yang, and Pandey (2012) x Desmarais and Gamassou (2014) x Giauque, Ritz, Varone, and AnderfuhrenBiget (2012) x x…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table A2 categorizes the same articles based on the measure of PSM used in each study. The columns are as follows: Alonso and Lewis (2001) x Andersen (2009) x Andersen and Pedersen (2012) x Andersen and Serritzlew (2012) x Bellé (2013) x x x x Brewer and Selden (1998) x Brewer, Selden, and Facer (2000) x Bright (2005) x Bright (2007) x Caillier (2013) x Caillier (2014) x Christensen and Wright (2011) x x x Coursey, Yang, and Pandey (2012) x Desmarais and Gamassou (2014) x Giauque, Ritz, Varone, and AnderfuhrenBiget (2012) x x…”
Section: Resultsmentioning
confidence: 99%
“…Other methods are identified. (2012) 3D 13i Andersen and Serritzlew (2012) 1D 4i Bellé (2013) x Brewer and Selden (1998) 1D 3i Brewer, Selden, and Facer (2000) 6D 40i Q-methodology Bright (2005) x Bright (2007) x Caillier (2013) x Caillier (2014) Christensen and Wright (2011) x Coursey, Yang, and Pandey (2012) x Desmarais and Gamassou (2014) x Giauque, Ritz, Varone, and AnderfuhrenBiget (2012) 4D 11i Houston (2011) 1D 2i Johnson (2012) 2D 7i Kim (2012) 4D 20i Kim et al (2013) x Kjeldsen (2012) 3D Semistructured Interview Kjeldsen (2014) 3D 11i Survey and interview Liu and Tang (2011) 3D 12i Liu, Tang, and Zhu (2008) x Liu, Tang, and Yang (2013) 3D 12i Liu, Yang, and Yu (2014) 4D 18i Moynihan and Pandey (2007) 2D 7i Pandey, Wright, and Moynihan (2008) x Park and Rainey (2008) 1D 6i Perry (1996) x Perry (1997) x Petrovsky and Ritz (2013) 4D 10i Ritz (2009) x 2D 5i Steijn (2008) 1D 1i Taylor (2008) 1D 2i Taylor (2010) 1D 5i van Loon, Leisink, and Vandenabeele (2013) 4D 15i Vandenabeele (2008b) 3D 13i Vandenabeele (2009) 5D 18i Vandenabeele and Van de Walle (2008) 3D 5i Ward (2014) 3D 13i Wright, Moynihan, and Pandey (2012) x Wright and Pandey (2008) x Wright and P...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examining motivational attributes in the public sector as well as possible differences among the generation groups, this study will search also for variances among hierarchical position and gender. In terms of hierarchical position, a small proportion of research has been performed, indicating a positive relationship with Public Service Motivation (PSM) (Desmarais & Gamassou, 2014). Indeed, Desmarais and Gamassou (2014) concluded that there are disparities in motivation in relation to hierarchical level, placing emphasis on the division of personnel management policies in public institutions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In terms of hierarchical position, a small proportion of research has been performed, indicating a positive relationship with Public Service Motivation (PSM) (Desmarais & Gamassou, 2014). Indeed, Desmarais and Gamassou (2014) concluded that there are disparities in motivation in relation to hierarchical level, placing emphasis on the division of personnel management policies in public institutions. Moreover, Camilieri's study (2007) found that the more an employee raises in the institution's hierarchy, the more the PSM is reinforced.…”
Section: Theoretical Backgroundmentioning
confidence: 99%